Effects of probiotic supplementation on bone health in postmenopausal women: a systematic review and meta-analysis - Wang, Fang; Wei, Wei; Liu, Peng Ju (Frontiers in Endocrinology, 2024)
The beneficial effects of probiotic supplementation on bone health in postmenopausal women require further validation.Objective: This study systematically reviewed and conducted a meta-analysis of randomized controlled trials (RCTs) to assess the relationship between probiotic supplementation and changes in bone mineral density (BMD) and bone turnover markers (BTMs) among postmenopausal women.Methods: A systematic search was conducted across four databases to retrieve data on lumbar spine BMD, hip BMD, collagen type 1 cross-linked C-telopeptide (CTX), receptor activator of nuclear factor-κB ligand (RANKL), osteocalcin (OC), osteoprotegerin (OPG), N-terminal propeptide of type 1 procollagen (P1NP), and bone-specific alkaline phosphatase (BALP) in postmenopausal women. Eligible RCTs were quantitatively analyzed using random-effects meta-analyses. Additional analyses, including subgroup, sensitivity, and meta-regression analyses, were performed.Results: Twelve RCTs involving 1183 postmenopausal women were included. Compared with the control group, postmenopausal women who received probiotic supplementation showed significantly greater BMD in both the lumbar spine (standardized mean difference [SMD] = 0.60, 95% confidence interval [CI] 0.14 to 1.05) and the hip (SMD = 0.74, 95%CI 0.15 to 1.33).Additionally, probiotic supplementation was associated with reduced levels of CTX (SMD = -1.51, 95%CI -1.88 to -0.41) and BALP (SMD = -1.80, 95%CI -2.78 to -0.81). No significant differences were found between the probiotic and control groups in terms of other BTMs.Subgroup analyses revealed that the increase in BMD due to probiotic supplementation was 3 more significant in postmenopausal women with osteopenia than in those with osteoporosis. The meta-analysis results for both lumbar spine and hip BMD remained robust after conducting sensitivity analyses and meta-regressions.Supplementation with probiotics may increase BMD among postmenopausal women, with stronger evidence in women with osteopenia than osteoporosis. Further RCTs are suggested to confirm and refine these findings.